Upaya Unit PKP-PK Dalam Meningkatkan Kualitas Sumber Daya Manusia Di Bandar Udara Tunggul Wulung Cilacap - M. Agil Septiyana Putra; Hodi (Jurnal Kajian dan Penelitian Umum, 2023)
The airport is one of the systems in the air transportation system which has a role as one of the important supporting elements in development in all fields, the Aviation Accident Assistance Unit and fire fighting (PKP-PK) at the stump wulung airport, Cilacap, are still not supported by human resources. Competent Human Resources (HR). The goal to be achieved in this study is to find out the efforts made by the PKP-PK unit for its personnel to improve the quality of Human Resources (HR). This study uses a qualitative approach, where qualitative research as a scientific method is often used and carried out by a group of researchers in the field of social sciences, including education. Qualitative research is conducted to build knowledge through understanding and discovery. The results of this study indicate that the efforts made by the PKP-PK unit to improve the quality of human resources include: 1) providing personnel motivation 2) coaching 3) conducting training 4) customizing work 5) providing supporting facilities 6) supervision 7) awards 8 ) conduct periodic performance evaluations. And the suitability of the quality of human resources in this study are 1) lack of discipline in personnel 2) fitness equipment or sports facilities are damaged 3) whatc room cannot be used yet.